Policy on Reducing Child Labor as the Elimination of the Worst Forms of Child Labor - Errika Putri Anggriani (Unnes Law Journal, 2020)
The more complex issue of child labor now a days because many children work at school age. Child labor vulnerable to be exploitated, doing hazardous work, mor a land psychological, and hampered to access education. So the government issued a policy Reduction of Child Labour in order to Support the Family Hope Program (PPA-PKH) as efforts to Elimination of the Worst Forms of Child (PBPTA) in order for the child can be returned in the educational unit, Pemalang is one of the districts that run the program PPA -PKH. Problems examined: (1) Implementation of PPA-PKH asefforts of PBPTA in Pemalang (2) Obstacles and over coming obstacles in the implementation of PPA-PKH policiesas PBPTA efforts in Pemalang. This study using sociological juridical approach. Results of the study (1) Implementation of policies PPA-PKH in Pemalang has been run in accordance with the purpose, with the establishment of shelters through three stages: pre shelter, the implementation in the shelter, and after the implementation form shelter and get a recommendation schools (2) Efforts to overcome the obstacles in the implementation of PPA -PKH policies in Pemalang which includes the beneficiaries of data was only 10% valid so that need to perform additional data. Inability of companionon the shelter so tha this attemptstomake psycologis approachand change the way of learning. Lack of coordination between relevant government service to coordinate their efforts and commitment among relevant government service and proposing a scholarship program for the children of beneficiaries. The advice given by the researchers that the data of beneficiaries must be renewed every year, provide socialiszation that bring about beneficiary families about the importance of education impact economic development of families, increased coordination between relevant government service, there is certainly that the child gets a scholarship or BSM for education.